Description of Two New Species of Gonatopus Ljungh from Argentina (Hymenoptera: Chrysidoidea: Dryinidae) - Virla, Eduardo Gabriel (2008)
Two new species of the genus Gonatopus Ljungh from Argentina are described: G. saltensis new species, from Salta, El Quebrachal, and G. hermosensis new species, from Buenos Aires, Monte Hermoso.